An unmarried woman [videorecording (DVD)] - Mazursky, Paul; Clayburgh, Jill; Bates, Alan, 1934-2003; Murphy, Michael, 1938-; Quinn, Patricia, 1937-; Bishop, Kelly (Criterion collection, 2020)
One woman's journey of self-discovery brings about a warmly human cultural conversation about female liberation, in this wonderfully frank, funny chronicle of changing '70s sexual politics by Paul Mazursky. When her husband of sixteen years abruptly leaves her for a younger woman, Manhattan gallery worker Erica finds herself alone and adrift, but also newly empowered to explore her needs and desires as she tests the waters of a new relationship with a charismatic artist.